Rehabilitation of child labourers in India - Pati, R. N. (ed.) (New Delhi, 1991)
Millions of Children in many developing countries are adversely affected by inadequate basic health facilities, shelter, education, material resources and nutrition available for their improved living. Governments in developing countries have failed to achieve desired objectives set up for promotion of universal child immunization, oral rehydration therapy for prevention of 2.5 million deaths every year, combating acute respiratory infections and major opportunities provided through various welfare programmes for the children. The year 1990 has witnessed an important international event, i.e., World Summit of Children, which has not only emphasized on revision of goals adopted in child welfare programmes but also sensitized the governments and politicians of developing countries for ensuring protection and development of children all over the world. Jan Marteson, Under-Secretary-General for Human Rights, U.N. has rightly observed that "respect and protection of all the children's rights are the starting point for the full development of the potential of the individual in an atmosphere of freedom, dignity and justice." The problems of children are deep rooted in the family and its socio-cultural environment which influence the parental attitude towards upbringing of their children. In many communities the children lack protective caring. The way the parents up bring their children indicates the social value on children and their commitment towards the development of future generation. It is a well recognized fact that development of any country as well as population very much depends on enhancing the human conditions of their children.
Keywords: Economic